2013
DOI: 10.1542/peds.2013-1780
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Interstitial Lung Diseases: An 18-year Retrospective Analysis

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Childhood interstitial lung diseases occur in a variety of clinical contexts and are associated with high morbidity and mortality. Advances in the understanding of disease pathogenesis and use of standardized terminology have facilitated increased case ascertainment. WHAT THIS STUDY ADDS:This study demonstrates that cases of newly described forms of childhood interstitial lung diseases likely occur at all children' s hospitals. With advances in genetic testing and recognition of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 24 publications
4
48
0
Order By: Relevance
“…In the Royal Brompton series, one case of UIP was found post mortem in an 18-year-old man before the availability of testing for surfactant mutations and with no clinical information (13). Similar to our study, no IPF/UIP cases were found in the Vanderbilt series (16). Therefore, IPF with UIP phenotype has not been convincingly demonstrated in a child.…”
Section: Original Researchsupporting
confidence: 62%
See 2 more Smart Citations
“…In the Royal Brompton series, one case of UIP was found post mortem in an 18-year-old man before the availability of testing for surfactant mutations and with no clinical information (13). Similar to our study, no IPF/UIP cases were found in the Vanderbilt series (16). Therefore, IPF with UIP phenotype has not been convincingly demonstrated in a child.…”
Section: Original Researchsupporting
confidence: 62%
“…We propose two factors that explain these differences: (1) our study included only biopsied children and (2) our study included both ICM and ICT patients. In the 18-year retrospective review of 93 chILD cases from Vanderbilt Children's Hospital, Soares and colleagues found that, with newer noninvasive techniques, almost one third could be diagnosed without lung biopsy (16). Compared with the Vanderbilt study, which included biopsied and nonbiopsied children of all ages, the mortality of biopsied children in our combined studies (,2 and 2-18) was twice as high (16.1 vs. 32.3%).…”
Section: Original Researchmentioning
confidence: 67%
See 1 more Smart Citation
“…The need for multicenter collaboration to improve approaches to diagnosis and treatment of children with these disorders has resulted in the formation of research networks, including the Children's Interstitial Lung Disease Research Network in North America and the Children's Interstitial Lung DiseaseEuropean Union. Several recent studies suggest that childhood interstitial lung disease is often underrecognized 3,4 and associated with high health-care resource utilization. 1 One primary area of progress is recognition that the forms of diffuse lung disease affecting children aged < 2 years are often distinct from the forms most common in adults.…”
mentioning
confidence: 99%
“…These imaging findings, in conjunction with an appropriate clinical context, are now considered sufficient for NEHI diagnosis, per American Thoracic Society clinical guidelines (8). Although these radiologic findings are believed to be specific for NEHI when observed and have been used to retrospectively identify cases (9), atypical imaging is present in some cases subsequently diagnosed by biopsy (7). Chest CT patterns in adults with NEHI have not been characterized to date.…”
mentioning
confidence: 99%